Diagenetic compaction experiments on simulated anhydrite fault gouge under static conditions. Issue 5 (15th May 2014) - Pluymakers, Anne M. H.; Peach, Colin J.; Spiers, Christopher J.
Abstract: Faults that crosscut subsurface CO2 storage systems offer potential leakage pathways, especially if fault reactivation and dilation occur. After reactivation, however, newly formed fault gouge is expected to gradually compact and seal as a function of time. To estimate the time scale on which this occurs, the processes that control compaction must be understood. We performed uniaxial compaction experiments on simulated anhydrite fault gouge to investigate the deformation mechanisms that operate under postslip conditions in faulted anhydrite caprocks. This involved constant stress (5–12 MPa) and stress stepping experiments (5/7.5/10 MPa) performed at 80°C, under dry and wet conditions, on fault gouge samples prepared from crushed natural anhydrite sieved into different grain size fractions in the range 20–500 µm. Dry samples showed little to no compaction creep, whereas wet samples (i.e., flooded with presaturated CaSO4 solution) showed rapid compaction. Our mechanical data and microstructural observations on wet samples suggest that for fine grain sizes (<50 µm) and low stresses, gouge compaction is controlled by diffusion‐controlled pressure solution. With increasing grain size and stress, fluid‐assisted subcritical microcracking becomes dominant. Pressurizing solution‐flooded samples with CO2 (15 MPa) led to no significant effect on compaction rates in fine‐grained material, but it decreased compaction rates in coarse samples. Since fine grain sizes are expected in reactivated faults, we infer that pressure solution will dominate in anhydrite (cap)rocks, with extrapolation of our lab data to reservoir conditions suggesting sealing time scales of a few decades. Key Points: Compaction rate of anhydrite fault gouge studied at upper crustal P‐T conditions Fine gouges compact via pressure solution, coarse ones via microcracking Extrapolations to nature predict that faulted anhydrite seals in a few decades